Pediatric dyslipidemia. (June 2022) - Maldonado, Victoria; Weeks, Bevin; Cho, Michael; Turpin, Dima; Arevalo, Alejandro
Abstract: Background: In the United States, cardiovascular disease is the number one cause of morbidity and mortality. 1, 2 Hyperlipidemia contributes to adverse cardiac outcomes through the formation of atherosclerotic plaques. Pediatric dyslipidemia has been linked to the development of atherosclerotic plaques at an early age, subsequently increasing the risk of premature cardiovascular adverse events. 1 While many pediatric patients with dyslipidemia have predispositions that influence their risk for disease development, patients without these predispositions can also develop lipid abnormalities that otherwise would not be suspected. 2 Over the years, guidelines have been inconsistent regarding screening for dyslipidemia in the pediatric population. Aim of review: We performed a literature review and discussed our institutional approach to screening and managing pediatric dyslipidemia. Key scientific concepts of review: We discuss genetic testing in pediatric dyslipidemia as well as a two-tier approached to management. Highlights: Pediatric dyslipidemia incidence is between 13-20%. Pediatric dyslipidemia universal screening is recommended. Initial pediatric lipid management is geared toward lifestyle changes, followed by pharmacotherapy.